(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Visarpa is one of the major Skin disease which is widely explained in our Ayurvedic classics. The clinical features contemplates with Herpes Zoster which is an active transmitting Viral disease. This case reports shows the Successful treatment of Visarpa. Here presenting a case of 72 year, female with sudden onset of 2-3 Vesicles on an Erthyematous base over the chin and left half of the lower lip, along with dragging pain and burning sensation within 2 days. Gradually Vesicles started to appear over the left side of the face, left Ear, Tongue with increased number of Vesicles within 4-5days along with other symptoms persists. Clinically the patient was diagnosed as Visarpa (Herpes Zoster). As Pitta Dosha and Raktha Dhathu vitiation was noticed, managed by Siravyadha as Shodhananga chikitsa and the Dravyas with Tiktha Rasa, Sheetha veerya in nature. The patient showed improvement within 15days of Treatment. The detailed case is presented in the full paper.